Histopathological and ultrastructural changes in the rats brain after air shock wave impact - S.V. Kozlov; Yu.V. Kozlova; N.S. Bondarenko; O.O. Bondarenko (Medičnì Perspektivi, 2024)
The using of explosive substances and devices can lead to brain injuries, the diagnosis of which requires the determination of primary biomarkers. Therefore, the aim was to establish and study histopathological and ultrastructural changes in the rats brain after exposure to an air blast wave. The study was carried out on 18 male Wistar rats, which were randomly divided into two groups: sham (n=9) and experimental (n=9). The animals of the experimental group were anesthetized with halothane and gently fixed in a horizontal position on the abdomen with the front part of the rat's muzzle at a distance of 5 cm from the device opening and subjected to an excess pressure of 26-36 kPa. Animals of both groups were decapitated, brains were removed, fixed, histopathological and ultrastructural analyzes were conducted using standard methods. Intergroup differences were assessed by Mann-Whitney U-test. Light microscopy revealed primary lesions in the form of small focal, multifocal hemorrhages, cerebral vessel ruptures and microscopic ruptures of the brain substance. In almost all brain samples, there is a significant saturation of the venous vessels with the presence of erythrocyte stasis. Violation of the blood-brain barrier, the presence of edema of the perivascular space, and petechial hemorrhages in the neuropil were registered ultrastructurally. Based on the study results, a morphological algorithm for assessing primary histostructural intracranial brain injuries and their consequences after exposure to an air shock wave was proposed. The injuries were found to be caused by the direct traumatic effect of the air shock wave. In the acute post-traumatic period, histopathological and ultrastructural changes in the brain can manifest as changes in neurons and in the blood-brain barrier and be accompanied by perivascular multifocal small-focal hemorrhages, neuropil ruptures, edema of pericellular and perivascular spaces, which together can be considered as biomarkers of primary traumatic changes after exposure to an air shock wave.